Glomerular endothelial cells eliminate nicotinamide adenine dinucleotide to instruct CD103 + T cells in human lupus nephritis - Li Jia; Mengdi Liu; Huiyan Ji; Jiaxin Lei; Danhua Su; Lingyi Li; Ting Liu; Fenghong Yuan; Lin Xu; Qinghua Cao; Huimin Zhang; Zhenke Wen (Proceedings of the National Academy of Sciences, 2025)
Lupus nephritis (LN), which is characterized by the accumulation of DNA-containing immune complexes (ICs), is the leading cause of death in patients with systemic lupus erythematosus (SLE). While growing evidence highlights the central role of CD103 + T cells in shaping the immune landscape of regional tissues, mechanisms driving the cell differentiation in LN remain largely unexplored. In this study, we identified an increased frequency of CD4 + CD103 + T cells within the kidneys of SLE patients. Importantly, glomerular endothelial cells (ECs) from human LN tissues were found to promote the differentiation of CD4 + CD103 + T cells by upregulating B lymphocyte–induced maturation protein 1 (Blimp-1). Genetic knockdown of Blimp-1 in CD4 + T cells resulted in a reduced frequency of renal CD4 + CD103 + T cells and alleviated LN in humanized SLE chimeras. Mechanistically, LN-associated ECs, triggered by circulating DNA from SLE patients, exhibited elevated CD38 expression via the cGAS-STING signaling pathway. This facilitated the transfer of CD38 into CD4 + T cells through an exosome-dependent mechanism, leading to the depletion of nicotinamide adenine dinucleotide (NAD + ) levels in CD4 + T cells. The resulting NAD + depletion impaired the PARP1-mediated ADP-ribosylation of early growth response protein 1 (EGR1), which, in turn, enhanced Blimp-1 transcription and promoted CD103 + T cell differentiation. Targeting the cGAS/STING-CD38-EGR1 axis effectively reduced renal CD103 + T cell accumulation and inhibited LN progression in humanized SLE chimeras. Thus, ECs facilitate NAD + depletion to drive CD103 + T cell differentiation, presenting a cellular mechanism underlying LN pathogenesis and a potential therapeutic target for the clinical management of human LN.